(untitled) (Global Journal of Human-Social Science, 2020)
The article discusses current trends in the development of scientific knowledge regarding the management of natural resources. The role of the "tragedy of the commons" in the management of natural resources is revealed. An overview of the causes and consequences of corruption in relations "power-society-natural resources" is given. Fish resources are taken as an example.